Aspects of source rock evaluation and diagenetic history of the akinbo' shale eastern dahomey basin, southwestern Nigeria (2006)
"The Akinbo Formation comprises a sequence of mostly dark, pale-greenish grey, laminated shale, slightly glauconitic shale, sandy shale with subordinate claystone lenses. Selected subsurface samples of the shaly facies as penetrated by Akinside 1582 well in eastern Dahomey basin, were investigated by sedimentological, mineralogical and geochemical parameters to ascertain the hydrocarbon potential and deduce the influence of variations of clay mineral indicators on the prospect. Values of total organic carbon (TOC) range from 0.46 to 1.98wt. % while the soluble organic matter (SOM) ranges from 71 to 1940 ppm and portrays that the organic matter is fair to good and adequate. Bitumen ratios have values of 15.25 to 98.98mg ext/gTOC which suggest that the sediments are immature to marginally mature. Average major elemental composition indicates 68.08% SiO2 17.55% Alc23. 4.07%K2O, 1.82%CaO, 1.57%Na2O, 1.29%MgO,• 0.62%Fe,03 and 0.50%MnO. A moderate increase in K2O from 2.26 to 4.92wt. % with depth was observed and this corresponds with increase in illite content. Equally, an increase in AI203/ (Fe203 + MgO) ratio from 7.27 to 22.07 with depth points to increasing diagenetic conditions. Illite and illite/smectite (mixed layer clays) dominate the clay mineral assemblage (>50%) while kaolinite and smectite (ca.35%) are comparatively low. Kaolinite and smectite were observed to disappear with depth as well as an increase in illite crystallinity. Smectite disappearance occurs at approximately vitrinite reflectance of 0.5 %(VRo) and illite crystallinity values are from 0.16 to 1.6°20 , which are within values of normal burial diagenesis. It can be deduced that the shale is a potential source rock varying from immature to marginally mature with prospects to generate gas rather than oil at appropriate thermal maturity. The clay mineral diagenetic indicators show that the hydrocarbon potential might have been affected by geothermal and tectonic history. "